Crystal structure of 6-hydroxy-5H-pyrrolo[3,4-b]pyrazine-5,7(6H)-dione, C6H3N3O3 - Yu Hui; Xu Feng (Zeitschrift für Kristallographie - New Crystal Structures)
C6H3O3N3, monoclinic, P21/n a = 5.0505(3) Å, b = 8.7139(6) Å, c = 14.2723(9) Å, β = 90.226(1)°, V = 628.11 Å3, Z = 4, R gt(F) = 0.0326, wR ref(F 2) = 0.1347, T = 296(2) K.